Results of Salmonella typhi culture in patients with suspected typhoid fever, treated in the Department of Child Health Medical School, Padjadjaran University, Hasan Sadikin General Hospital Bandung - Nanan Sekarwana; Herry Garna; Azhali M. S. (Indonesian Pediatric Society, 1989)
From October to December 1984, examination has been carried out on Salmonella typhi cultures from blood, bone marrow, faeces and urine of 43 patients suffering from suspected typhoid fever treated in the Department of Child Health, Medical Schooll Hasan Sadikin General Hospital, Bandung.It was apparent that among these 43 patients, 51.2% were males and 48.8% females. The greater number of them were more than 5 years old (64.4%). The results of Salmonella typhi cultures were obtained Â from 65% of the patients, consisting of 65% positive cultures from bone-marrow and 40% positive cultures from blood that showed a statistically significant difference (p < 0.05).Likewise, the time for matter-sampling for the examinations was based on the culture results, both on blood-culture and that of bone-marrow, statistically a significant was found (p < 0.05), whereas the results of cultures based on previous vaccination history and the administration of chloramphenicol prior to treatment did not differ significantly.It was obviously clear that the results of bone-marrow culture were more successful compared to those from blood culture, so that it should necessarily be emphasized, as to these examinations on culture from each patient with suspected typhoid fever, especially those patients hospitalized during the third week of their illness.